VALUASI: NILAI SEBENARNYA VS NILAI TAK SEBENARNYA - Dr. Said kelana (Jurnal Manajemen, 2011)
The purpose of valuation is to find the intrinsic value of assets. It is performed by estimating the future value. There are a number of assumption required and methods applied for valuation. Consecuently, there are a wide range of value resulted by some valuation. That is difficult to find the true value of valuation.   Keywords: valuation, intrinsic value, discount model, relative model.